Importance Performance Analysis of Factors Causing Reworks in the Construction Industry - Andi Andi; Jani Rahardjo; Fendy Fendy (Institute of Research and Community Outreach - Petra Christian University, 2020)
Rework can bring negative effect to construction project. This research aims to identify the importance level of factors causing reworks in structural, finishing, and mechanical, electrical and plumbing (MEP) works by a way of importance performance analysis (IPA). In order to reach this objective, the research evaluates the degree of occurrence the factors in each type of works and analyzes the level of difficulty in preventing the occurrence of the factors. The results are based on questionnaire survey, involving general and MEP contractors in Surabaya. Design related factors are the most frequent and most difficult to prevent in structural and finishing works. In MEP works, the most frequent factors are tight construction duration and unclear instructions from owner and designer; whilst insufficient owner’s capital is the most difficult to prevent. The research finds two factors that have high importance level, i.e. design changes and insufficient detail drawings.